Pengembangan Video Pembelajaran Berbantuan Canva Materi Cahaya Dengan Penguatan Karakter Mandiri Siswa Kelas IV Sekolah Dasar - Erlin Meilina Purwati; Sukamti Sukamti; Arda Purnama Putra (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2022)
Abstract: The purpose of this study is to produce Canva-assisted learning video media on light material with independent character strengthening for grade IV elementary school students that is valid according to material experts, media experts, and teachers, and is of interest to teachers and students. This research and development applies the Borg and Gall model which consists of 10 stages. Canva-assisted learning media is presented in the form of learning videos that present materials and guidelines for conducting experiments independently so that it can help students develop independent characters, and is equipped with a combination of animation, images, text, and sound. Product validity tests are carried out by material experts, media experts, and users (teachers). The trial was carried out on 21 grade IV students of SDN Sananwetan 1 Kota Blitar. The results of product validation from material experts obtained a value of 90 percent, media experts by 93.75 percent, users (teachers) by 94.4 percent and belong to the very valid category. As for the attractiveness aspect test, students get a score of 99.4 percent. Canva-assisted learning video media on light material with independent character strengthening for grade IV elementary school students can be said to be very valid according to material experts, media experts, and users (teachers), and is very attractive to teachers and students, so it can be used as a medium in learning. Abstrak: Tujuan penelitian ini adalah untuk menghasilkan media video pembelajaran berbantuan Canva pada materi cahaya dengan penguatan karakter mandiri untuk siswa kelas IV SD yang valid menurut ahli materi, ahli media, dan guru, serta menarik bagi guru dan siswa. Penelitian dan pengembangan ini menerapkan model Borg and Gall yang terdiri dari 10 tahapan. Media pembelajaran berbantuan Canva disajikan dalam bentuk video pembelajaran yang menyajikan materi dan pedoman untuk melakukan percobaan secara mandiri sehingga dapat membantu siswa mengembangkan karakter mandiri, serta dilengkapi dengan kombinasi antara animasi, gambar, teks, dan suara. Uji kevalidan produk dilakukan oleh ahli materi, ahli media, dan pengguna (guru). Uji coba pemakaian dilakukan kepada 21 siswa kelas IV SDN Sananwetan 1 Kota Blitar. Hasil validasi produk dari ahli materi diperoleh nilai sebesar 90 persen, ahli media sebesar 93,75 persen, pengguna (guru) sebesar 94,4 persen dan termasuk kategori sangat valid. Sedangkan untuk uji aspek kemenarikan dari siswa mendapatkan nilai sebesar 99,4 persen. Media video pembelajaran berbantuan Canva pada materi cahaya dengan penguatan karakter mandiri untuk siswa kelas IV SD dapat dikatakan sangat valid menurut ahli materi, ahli media, dan pengguna (guru), serta sangat menarik bagi guru dan siswa, sehingga dapat digunakan sebagai media dalam pembelajaran.